Pengaruh Media Lingkungan terhadap Minat Belajar IPAS Siswa Kelas IV SD Al-Khairaat Mamboro - Harizkayanti .S; Mahfud Mahmud Gamar; Pahriadi (JURNAL DIKDAS, 2026)
This study aims to determine the effect of using environment-based learning media on students' learning interest in the IPAS subject in grade IV at SD Alkhairaat Mamboro, which is motivated by low student learning interest and the limited use of innovative learning media in the school. This research is a quantitative study with a one-group pretest-posttest design involving 27 students as research samples selected through a purposive sampling technique. Data were collected using learning interest questionnaire instruments, observations, and documentation, which were then analyzed using the Paired Sample T-Test. The results showed a significant increase in learning interest, where the mean pretest score of 25.62 increased to 43.62 in the posttest, with an increase of 18 points. Based on statistical tests, the obtained t-value (20.448) was higher than the t-table (1.70562) with a significance value of 0.000 < 0.05. Therefore, it can be concluded that the use of environment-based learning media has a significant influence on students' learning interest in the IPAS subject in grade IV of SD Alkhairaat Mamboro.